Study on MEV90 of 0.5% ropivacaine for US-guided caudal epidural block in anorectal surgery - Zhang, Pei; Chang, Hong; Yang, Taoran; Fu, Yalong; He, Xuemei; Li, Jun; Yang, Mingan; Wang, Rurong; Li, Xuehan (Frontiers in Medicine, 2023)
Background Choosing the appropriate concentration and volume of anesthetics is critical for a successful nerve block. The current study aimed to determine the minimum effective volume (MEV) of 0.5% ropivacaine for US-guided CEB in 90% of patients (MEV90) undergoing anorectal surgery. The aims were to reduce the occurrence of complications associated with a sacral blockade in anorectal surgery, broaden the indications for surgical procedures and treatment, and improve patient satisfaction. This study presents the groundwork for the development of individualized anesthetic programs. We believe that the study would serve as a reference for the use of caudal epidural block (CEB) in lower abdominal surgery for intraoperative and postoperative analgesia. Methods This study used a biased coin design (BCD) up-and-down method (UDM). We divided the participants into two groups based on gender, and each group independently performed the biased coin design up-and-down method. We used 0.5% ropivacaine for the first patient in each group; however, the volume was 10 ml for men and 8 ml for women. Therefore, the dose of anesthetics given to each patient was determined by the response of the previous patient. If the block of the previous patient failed, the volume was increased by 2 ml in the following patient. Otherwise, the next subject had an 11% chance of receiving a volume of 2 ml less or an 89% chance of receiving no volume change. We defined a successful block as painless surgery with anal sphincter relaxation 15 min after the drug injection. Enrollment was completed after 45 successful caudal blocks for each group. Results Caudal epidural block was successfully performed on 50 men and 49 women. The MEV90 of ropivacaine for CEB was calculated to be 12.88 ml (95% CI: 10.8–14 ml) for men and 10.73 ml (95% CI: 9.67–12 ml) for women. Men had a MEV99 of 13.88 ml (95% CI: 12.97–14 ml), and women had a MEV99 of 11.87 ml (95% CI: 11.72–12 ml). Conclusion With operability and general applicability, it is possible to increase the success rate of CEB for anorectal surgery to 99% as well as decrease the incidence of anesthesia-related complications. CEB can meet the needs of patients for rapid postoperative rehabilitation, improve patient satisfaction, and lay a solid foundation for postoperative analgesia.